Conjunctural fluctuations in the Russian economy - T. I. Gordievich; P. V. Ruzanov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of macroeconomic trends in 2020-2021 in Russia. The relevance of the problem is connected with the need to determine the nature of conjunctural fluctuations of macro indicators. Russia’s GDP in 2020 showed a decrease of 3,1 %, in 2021 it is expected to grow by 4,5 %. The crisis of 2020 was reflected in the disruption of reproductive chains and affected the level of production of certain economic sectors. Economic growth in 2021 had a restorative character. It appeared in the form of a revival of consumer demand and the resumption of production growth in the industries affected by the coronacrisis. The purpose of the study is to analyze the main macroeconomic indicators in the conditions of the coronavirus pandemic, to determine trends and patterns of economic development. The article uses methods of formal and meaningful analysis of statistical information. The present study shows that the conjunctural fluctuations of the economy are based on internal and external factors that stimulate and restrain economic growth. The trigger for the uneven development of the economy was a natural cataclysm in the form of a coronavirus pandemic.